Explicating the role of trust in knowledge sharing: a structural equation model test - Smaliukienė, Rasa; Bekešienė, Svajonė; Chlivickas, Eugenijus; Magyla, Marius (Journal of Business Economics and Management, 2017)
Although the large body of literature suggests that trust is a prerequisite for knowledge sharing, the understanding of mediational pathways remains limited. The paper fills the gap by combining two separate streams in knowledge sharing, where the first reflects the paradigm of the organizational behaviour theory and highlights the impact of organizational culture and employees’ trust; where the second one discloses the impact of technology deployment in knowledge sharing. Building on the premises that interdependence between variables that affect knowledge sharing raises form organizational culture of trust and available technologies, we examine the structural origins of knowledge sharing. As a method structural equation modelling test was used to analyse the data. Hypothesised five-factor model was tested through two stages using AMOS software. The findings carry theoretical implications for the knowledge management body of knowledge since they extended the research on knowledge sharing by integrating organisational culture and technological solutions into one complex system. Form practical perspective, the relationship among four predictors – trust in leadership, trust in co-workers, trust in technologies for knowledge management, and fear of losing one’s value – provide a proof on how organizations knowledge sharing is composed and how it could be developed.